Magnetic alloy / alumina composite thermal spraying powder and preparation method and application thereof
By covering the low-dielectric ceramic phase material on the magnetic alloy, adjusting the electromagnetic parameters and the thickness of the coating, the problems of high dielectric characteristics, poor impedance matching, fast settlement and easy oxidation during the thermal spraying process of commercial FSA are solved. It achieves efficient impedance matching, composition uniformity and oxidation resistance, and is suitable for high-temperature absorbing coatings.
Patent Information
- Application Number
- CN202211650238.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-21
AI Technical Summary
After the atomization molding of commercial ferrosilicon aluminum (FSA) has high dielectric characteristics, poor impedance matching characteristics, high density during granulation, easy to settle, resulting in uneven composition, easy oxidation during thermal spraying, and infrared emissivity of the coating Higher issues.
By using ceramic phase materials with low dielectric characteristics to coat magnetic alloys, electromagnetic parameters are regulated, and impedance matching characteristics are improved; by multiple cladding, the thickness of the cladding layer is adjusted, the settlement rate is reduced, and the uniformity of component distribution is achieved; by introducing multiple interfaces , reduce infrared emissivity; and improve the performance of high-temperature absorbing coating by regulating the slurry ratio during granulation.
Effectively improve the impedance matching characteristics of magnetic alloys, reduce the settlement rate, realize the uniform component distribution of composite powder, improve the oxidation resistance, and reduce infrared emissivity, solving the commercial FSA in the field of high-temperature absorbing coatings Application restriction issue.
Smart Images

Figure CN115846652B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal spraying materials and relates to a magnetic alloy / aluminum oxide composite thermal spraying powder and a preparation method thereof. Background Art
[0002] Thermal spraying technology is one of the most effective technologies for surface modification in the field of surface engineering. Depending on the coating materials and processes, functional coatings such as wear resistance, corrosion resistance, high temperature oxidation resistance, thermal barrier, electromagnetic shielding absorption, conductive insulation, infrared radiation, etc. can be prepared. The coating materials include metals, ceramics, plastics and their composite materials. They are usually divided into wire (rod) spray materials, powder spray materials, brazing materials and auxiliary materials according to their types. They are widely used in aerospace and national defense fields. Among them, powder spraying materials are the key raw materials of thermal spraying technology. Their sphericity, fluidity, impurity content, etc. largely determine the structure and performance of the final coating. At the same time, in order to meet the requirements of different metal powders under different conditions, according to their related properties, the main preparation methods include atomization, mechanical crushing, rotating electrode method, electrochemical corrosion method, reduction method, etc. Among them, gas atomization and rotating electrode methods can directly obtain spherical powders, and the powder prepared by gas atomization has a larger particle size range and is the most widely used. Gas atomization powder making is a complex multiphase flow coupling process. Different compositions and different particle sizes have corresponding fixed process parameters. Once the composition changes, the atomization parameters need to be adjusted. Therefore, the composition of industrialized atomized alloy powder is fixed after production, and further, its corresponding electromagnetic parameters are fixed.
[0003] Magnetic alloy FeSiAl (FSA) can be used as a magnetic loss absorber due to its excellent soft magnetic properties. It has been widely used and successfully commercialized. However, commercial FeSiAl (FSA) has high dielectric properties after atomization and poor impedance matching properties. It has high density and is easy to settle during granulation, resulting in uneven granulation composition. It is also easy to oxidize during thermal spraying and has high infrared emissivity of the coating. The composition of commonly used FSA fluctuates within a certain range around Sendust (85% Fe-9.6% Si-5.4% Al) alloy. At the same time, due to its high dielectric properties, its powder itself has poor impedance matching characteristics. In addition, mechanical alloying is often used to modify it to break through the Snock limit to improve its magnetic properties and to dope it with elements to improve its brittleness. However, the flattening of FSA during the mechanical alloying process further improves the dielectric properties of FSA, but the impedance matching characteristics are still poor. From the principle of thermal spraying, it can be seen that the flaky morphology is also the main morphology of the magnetic alloy in the coating after thermal spraying. This also makes the corresponding high-temperature stealth coating of FSA have poor absorbing performance, which greatly limits the application of FSA in the field of high-temperature absorbing coatings. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a magnetic alloy / alumina composite thermal spray powder and a preparation method and application thereof, so as to solve the problems of high dielectric properties and poor impedance matching characteristics of commercial iron silicon aluminum (FSA) after atomization molding, high density and easy sedimentation during granulation resulting in uneven granulation composition, easy oxidation during thermal spraying, and high infrared emissivity of the coating.
[0005] In order to achieve the above object, the present invention provides a method for preparing a magnetic alloy / aluminum oxide composite thermal spraying powder, comprising the following steps:
[0006] S1, SiO2 shell coating
[0007] Dissolve polyvinyl pyrrolidone PVP in deionized water by mechanical stirring, then add magnetic alloy powder and stir to react for a preset time, then heat up, add silicon particles, then drip ammonia solution of a prepared concentration into the mixture at a uniform speed through a peristaltic pump, and when the reaction is finished, obtain magnetic alloy @SiO2 by magnetic collection, and dry to obtain magnetic alloy @SiO2 powder;
[0008] S2, ZrO2 shell coating
[0009] Take ZrOCl2·8H2O and dissolve it in deionized water under mechanical stirring, then add the magnetic alloy @SiO2 powder obtained by S1, and then drip the prepared ammonia solution into the mixed solution at a uniform speed through a peristaltic pump. After the reaction is completed, the magnetic alloy @SiO2@ZrO2 is obtained by magnetic collection, and after drying, the magnetic alloy @SiO2@ZrO2 powder is obtained by heat treatment in an inert gas environment;
[0010] S3. Composite powder preparation
[0011] The magnetic alloy @SiO2@ZrO2 powder obtained by S2 and the ceramic binder Al2O3 are added to a ball mill, followed by polyvinyl alcohol (PVA) and then zirconium oxide balls, and the mixture is rolled and stirred to obtain a slurry; the obtained slurry is sent to a spray granulator for spray granulation, and the mixture is dried and sieved to obtain a magnetic alloy @SiO2@ZrO2 / alumina ceramic composite powder, namely a magnetic alloy / alumina composite thermal spraying powder.
[0012] Furthermore, in step S1, the magnetic alloy powder is a high Curie temperature iron-based magnetic alloy, and its particle size is less than 5 μm.
[0013] Furthermore, the high Curie temperature iron-based magnetic alloy is Sendust Aluminum (FSA).
[0014] Furthermore, in step S1, the molecular weight of PVP is K15-K40. PVP can be used as a surface surfactant and dispersant. The larger the molecular weight and the longer the molecular chain, the better the dispersibility of magnetic particles with a specific particle size. However, as the molecular chain grows, the surface of the coating layer will become rougher.
[0015] Furthermore, in step S1, the mass of the PVP is 1-5% of the magnetic alloy powder. The amount of PVP should be kept within an appropriate range. If the amount of PVP is too small, the coating layer will be uneven or there will be a large amount of exposed and uncoated. If the amount of PVP is too large, it will affect the roughness of the coating layer.
[0016] Furthermore, in step S1, the silicon particles are irregular silicon particles with a size of 5 to 10 mm. Silicon particles larger than 5 mm are conducive to filtering and collecting the magnetic coated powder after the reaction, and the filtered silicon particles can still be reused, thus avoiding waste of resources.
[0017] Furthermore, in step S1, the mechanical stirring rate is 300-500 r / min.
[0018] Furthermore, in step S1, the heating temperature is 70-85°C, the mass of silicon particles is 3-10% of the magnetic alloy powder, the concentration of ammonia solution is 0.1-0.15 mol / L, and the dripping rate of ammonia solution is 1-3 mL / min. The reaction temperature, the amount of silicon particles, and the amount of alkaline catalyst jointly determine the hydrolysis rate of silicon powder. According to the principle of heterogeneous nucleation, the hydrolysis rate should be kept within the range of preferential heterogeneous nucleation to avoid homogeneous nucleation of silicon oxide in the solution, otherwise a large number of free nano silicon oxide particles will be attached to the surface of magnetic alloy @SiO2 powder during magnetic collection, which is conducive to ensuring the collection purity of magnetic alloy @SiO2 powder.
[0019] Furthermore, in step S1, the drying temperature is 80-90°C.
[0020] Furthermore, in step S2, the concentration of ZrOCl2·8H2O is 0.06-0.1 mol / L, the concentration of ammonia water is 0.03-0.06 mol / L, and the dripping rate of ammonia water solution is 1-3 mL / min. The concentration of ZrOCl2·8H2O and the amount of alkaline catalyst jointly determine the hydrolysis rate of zirconium oxychloride. Since zirconium oxychloride is very easy to hydrolyze, the concentration of ammonia water should be controlled at a low level as much as possible, otherwise a large amount of gel will appear in the solution, which is not conducive to the collection purity of magnetic alloy @SiO2@ZrO2 powder.
[0021] Furthermore, in step S2, the drying temperature is 80-90°C.
[0022] Further, in step S2, the heat treatment conditions are: the gas environment is N2 atmosphere or H2 / Ar atmosphere, the treatment temperature is 300-650°C, and the heat treatment time is 2-4h. The purpose of the heat treatment is to pyrolyze the hydrated zirconium oxide in the coating layer into a ZrO2 ceramic shell. When the temperature is 350-500°C, ZrO2 is mainly amorphous and monoclinic. When it is above 500°C, amorphous zirconium oxide begins to transform into monoclinic zirconium oxide. At 650°C, FSA is DO3 phase, which has the maximum saturation magnetization.
[0023] Furthermore, in step S3, the solid content of the obtained slurry is 30-50%, wherein the volume proportion of the magnetic alloy is 20-30%, and the mass of the PVA is 2-5% of the sum of the mass of the magnetic alloy @SiO2@ZrO2 powder and the alumina.
[0024] Furthermore, in step S3, the added amount of zirconia balls satisfies a ball-to-material ratio of 3 to 5:1.
[0025] Furthermore, in step S3, the particle size of Al2O3 is less than 5 μm.
[0026] Furthermore, in step S3, the inlet and outlet temperatures of the spray granulator are controlled at 250° C. and 120° C., respectively, the feed rate is 35 mL / min, and the atomizer frequency is 25 Hz.
[0027] Furthermore, in step S3, the drying temperature is 80-90°C.
[0028] Furthermore, in step S3, the screening process is specifically as follows: passing through 32 μm and 100 μm sieves, the vibration amplitude of the vibrating screen is 80-95%, and the vibration time is 5-10 minutes.
[0029] Of course, the magnetic alloy / aluminum oxide composite thermal spraying powder prepared by the above method also falls within the protection scope of the present invention.
[0030] At the same time, the present invention also provides an application of the magnetic alloy / alumina ceramic composite thermal spraying powder for preparing a high temperature resistant multifunctional magnetic composite radar absorbing coating, the application comprising the following steps:
[0031] Step A: Determine particle size and fluidity:
[0032] The particle size and fluidity of the magnetic alloy / alumina ceramic composite powder are measured by a laser particle size analyzer and a Hall flow meter respectively;
[0033] Step B, atmospheric plasma spraying:
[0034] Use solvent to wash away the oil stains on the surface of the substrate, sandblast the substrate, and then fix the sandblasted substrate in the spraying range of the robotic arm, measure the powder feeding rate, set the robotic arm program, introduce the carrier gas, and then set the spraying power, carrier gas rate, arc starting gas rate, etc. After the setting is completed, preheat the substrate, and then spray the bonding layer and magnetic alloy / alumina ceramic composite powder in turn.
[0035] Furthermore, the substrate in step B is 304 stainless steel.
[0036] Furthermore, the solvent in step B is ethanol or acetone.
[0037] Furthermore, the powder feeding rate in step B is 13 g / min.
[0038] Furthermore, the robot arm program setting in step B includes the distance from the substrate, the step distance, and the number of cycles, and the distance between the robot arm nozzle and the substrate is preferably 12 cm.
[0039] Furthermore, the spraying power in step B is 55KW.
[0040] Furthermore, the carrier gas in step B is argon, nitrogen, and hydrogen, and the carrier gas rates of argon, nitrogen, and hydrogen are 4529.6, 2264.8, and 1698.6 L / min, respectively.
[0041] Furthermore, the bonding layer in step B is Ni@Al.
[0042] The beneficial effects of the present invention are as follows: compared with the prior art, the present invention regulates the electromagnetic parameters of the magnetic alloy by coating with a ceramic phase material having low dielectric properties, thereby improving the impedance matching characteristics of the magnetic alloy; the thickness of the coating layer is regulated by multiple coatings to reduce the sedimentation rate of the magnetic alloy, thereby making the magnetic-dielectric component of the composite powder evenly distributed; the density of the coating layer is regulated by multiple coatings to improve the oxidation resistance of the magnetic alloy; the infrared emissivity of the magnetic alloy powder is reduced by introducing multiple interfaces using different ceramic phase materials; and the performance of the corresponding composite powder and the high-temperature absorbing coating is improved by regulating the slurry ratio during the granulation process, thereby solving the problems of high dielectric properties and poor impedance matching characteristics of commercial iron silicon aluminum (FSA) after atomization molding, high density and easy sedimentation during granulation, resulting in uneven granulation components, and easy oxidation during thermal spraying, and high infrared emissivity of the coating. At the same time, the method of the present invention is simple in process operation and easy to carry out mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a SEM image of the powder obtained in step 2 of Example 1;
[0044] Figure 2This is a SEM image of the powder obtained in step 4 of Example 1;
[0045] Figure 3 This is a SEM image of the coating obtained in step 6 of Example 1;
[0046] Figure 4 This is the electromagnetic parameter diagram of the powder obtained in step 2 of Example 1;
[0047] Figure 5 This is the SEM image of the powder obtained in step 1 of Comparative Example 1;
[0048] Figure 6 This is the SEM image of the powder obtained in step 3 of Comparative Example 1;
[0049] Figure 7 This is a SEM image of the coating obtained in step 5 of Comparative Example 1;
[0050] Figure 8 This is the electromagnetic parameter diagram of the powder obtained in step 1 of comparative example 1;
[0051] Fig. 9 is the SEM image of FSA powder in Comparative Example 2;
[0052] Fig.10 This is the SEM image of the powder obtained in step 2 of comparative example 2.
[0053] Fig.11 This is a SEM image of the coating obtained in step 4 of Comparative Example 2;
[0054] Fig.12 It is the electromagnetic parameter diagram of FSA powder in comparative example 2;
[0055] Fig.13 VSM diagrams of the three powders of FSA, FSA@SiO2, and FSA@SiO2@ZrO2 in Example 1;
[0056] Fig.14 This is the reflectivity graph of the powder obtained in step 2 of Example 1;
[0057] Fig.15 This is the reflectivity graph of the powder obtained in step 1 of Comparative Example 1;
[0058] Fig.16 This is the reflectivity diagram of FSA powder in Comparative Example 2. DETAILED DESCRIPTION
[0059] The technical scheme of the present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary descriptions and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by known methods.
[0060] In the following examples, the FSA powder used was purchased from Changsha Tianjiu Metal Materials Co., Ltd. The product grade is FeSiAl, the particle size is <5 μm, and the density is 7.8 g / cm 3 , SEM results are as follows Fig. 9 The electromagnetic parameters are shown in Fig.12 As shown, the VSM results are Fig.13 As shown; the Al2O3 used is Al2O3 with a particle size of <5μm; the silicon particles used are irregular silicon particles with a size of 5 to 10mm; the PVP used has a molecular weight of K15 to K40.
[0061] Example 1
[0062] Step 1: SiO2 shell coating
[0063] 2g PVP was uniformly dissolved in 1L deionized water under mechanical stirring at 300r / min. After fully dissolved, 100g FSA was added and reacted at room temperature for 30min. Then, 10g silicon particles were added when the water bath was heated to 70℃. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, FSA@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times. It was dried at 80℃ for use. Its density was 7.2g / cm 3 , the VSM results are as follows Fig.13 shown.
[0064] Step 2: ZrO2 shell coating
[0065] 20g ZrOCl2·8H2O was uniformly dissolved in 1L deionized water under mechanical stirring at 300r / min. After being fully dissolved, FSA@SiO2 obtained in step 1 was added. Then, the prepared ammonia solution was uniformly added into the mixed solution by a peristaltic pump. The concentration of ammonia solution was 0.05mol / L, and the ammonia solution dropping speed was 2mL / min. The mixture was reacted for 2h. After repeated washing with deionized water and magnetic collection, it was dried at 80℃ and finally heat treated at 500℃ for 3h in N2 atmosphere to obtain FSA@SiO2@ZrO2, whose density was 6.9g / cm 3 , SEM results are as follows Figure 1 The electromagnetic parameter results are shown in Figure 4 The reflectivity results are shown in Fig.14 As shown, the VSM results are Fig.13 shown.
[0066] Step 3: Composite powder preparation:
[0067] The obtained FSA@SiO2@ZrO2 powder and high-temperature ceramic binder Al2O3 are added to a ball mill, wherein the volume ratio of FSA is 23%, and the solid content of the slurry is 50%. At 100°C, the PVA binder with a total mass of FSA@SiO2@ZrO2 and Al2O3 of 2.46% is fully stirred and dissolved in deionized water with a corresponding solid content, and after being evenly dissolved and mixed, it is added to a ball mill, and 1.0-1.2mm zirconia balls are added according to a ball-to-material ratio of 4:1. The slurry is rolled and stirred for 10 hours to obtain a slurry; the prepared slurry is spray granulated, the inlet and outlet temperatures are controlled at 250°C and 120°C respectively, the feed rate is 35mL / min, and the atomizer frequency is 25Hz to obtain a powder.
[0068] Step 4: Drying and sieving
[0069] The composite powder obtained in step 3 was dried at 80-90°C to remove the residual water vapor and then passed through 32 μm and 100 μm sieves to collect the powder with a particle size of 32-100 μm, thus obtaining FSA@SiO2@ZrO2 / alumina ceramic composite powder; the SEM results are shown in Figure 2 shown.
[0070] Step 5: Determine particle size and flowability
[0071] The composite powder collected in step 4 was measured for particle size and fluidity by a laser particle size analyzer and a Hall flowmeter, respectively. The laser particle size analyzer measured D50 of the composite powder to be 40.5 μm, D90 of the composite powder to be 75.2 μm, and fluidity of the composite powder to be 105 s / 50 g.
[0072] Step 6: Atmospheric plasma spraying
[0073] After washing the surface oil of the 304 stainless steel substrate with ethanol and acetone, the 304 stainless steel substrate was sandblasted, and then the sandblasted 304 stainless steel substrate was fixed in the spraying range of the robot arm. The powder feeding rate was measured to be 13g / min, and the robot arm program was set to include a distance of 12cm from the substrate, a step distance (mm) of 3*42, and a number of cycles (non-stop) of 6, etc. Then, the spraying power was set to 55KW, and the argon, nitrogen, and hydrogen rates were 4529.6, 2264.8, and 1698.6L / min, respectively. After the setting was completed, the substrate was preheated, and then the bonding layer Ni@Al and the FSA@SiO2@ZrO2 / alumina ceramic composite powder functional layer were sprayed successively. The SEM results are shown in FIG. Figure 3 shown.
[0074] Comparative Example 1
[0075] Step 1: SiO2 shell coating
[0076] 2g PVP was uniformly dissolved in 1L deionized water under mechanical stirring at 300r / min. After it was fully dissolved, 100g FSA was added and reacted at room temperature for 30min. Then, 10g silicon particles were added when the water bath was heated to 70℃. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, FSA@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times. FSA@SiO2 powder was obtained by drying at 80℃. The SEM results are as follows: Figure 5 As shown, the electromagnetic parameter diagram is as follows Figure 8 The reflectivity results are shown in Fig.15 shown.
[0077] Step 2: Composite powder preparation:
[0078] The FSA@SiO2 powder obtained in step 1 and the ceramic binder Al2O3 are added to a ball mill, wherein the volume ratio of FSA is 23%, and the solid content of the slurry is 50%. At 100°C, the PVA binder (the sum of the mass of FSA@SiO2 and Al2O3, 2.46%), is fully stirred and dissolved in deionized water with a corresponding solid content. After being evenly dissolved and mixed, the mixture is added to a ball mill, and 1.0-1.2 mm zirconium oxide balls are added at a ball-to-material ratio of 4:1. The mixture is rolled and stirred for 10 hours to obtain a slurry. The prepared slurry is spray granulated, and the inlet and outlet temperatures are controlled at 250°C and 120°C, respectively. The feed rate is 35 mL / min, and the atomizer frequency is 25 Hz to obtain a composite powder.
[0079] Step 3: Drying and sieving
[0080] The composite powder obtained in step 2 was dried at 80-90°C to remove the residual water vapor and then passed through 32μm and 100μm sieves to collect the powder with a particle size of 32-100μm, thus obtaining FSA@SiO2 / alumina ceramic composite powder. The SEM results are as follows: Figure 6 shown.
[0081] Step 4: Determine particle size and flowability
[0082] The composite powder collected in step 3 was measured for particle size and fluidity by a laser particle size analyzer and a Hall flowmeter, respectively. The laser particle size analyzer measured D50 of the composite powder to be 43.2 μm, D90 of the composite powder to be 74.5 μm, and fluidity of the composite powder to be 112 s / 50 g.
[0083] Step 5: Atmospheric plasma spraying
[0084] After washing away the oil on the surface of the substrate with ethanol, acetone, etc., the substrate is sandblasted, and then the sandblasted substrate is fixed in the spraying range of the robotic arm. The powder feeding rate is measured to be 13g / min, and the robotic arm program is set to include a distance of 12cm from the substrate, a step distance (mm) of 3*42, and a number of cycles (non-stop) of 6, etc. Then, the spraying power is set to 55KW, and the argon, nitrogen, and hydrogen rates are 4529.6, 2264.8, and 1698.6L / min, respectively. After the setting is completed, the substrate is preheated, and then the bonding layer Ni@Al and the FSA@SiO2 / alumina ceramic composite powder functional layer are sprayed successively. The SEM results are shown in FIG. Figure 7 shown.
[0085] Comparative Example 2
[0086] Step 1: Composite powder preparation:
[0087] The obtained FSA powder and ceramic binder Al2O3 are added to a ball mill, wherein the volume ratio of FSA is 23%, and the solid content of the slurry is 50%. The PVA binder with a total mass of 2.46% of FSA and Al2O3 is fully stirred and dissolved in deionized water with a corresponding solid content at 100°C, and after being uniformly dissolved and mixed, it is added to the ball mill, and 1.0-1.2mm zirconium oxide balls are added according to a ball-to-material ratio of 4:1, and the slurry is rolled and stirred for 10 hours to obtain a slurry; the prepared slurry is sprayed and granulated, and the inlet and outlet temperatures are controlled at 250°C and 120°C respectively, the feed rate is 35mL / min, and the atomizer frequency is 25Hz to obtain a powder;
[0088] Step 2: Drying and sieving
[0089] The composite powder obtained in step 1 was dried at 80-90°C to remove the residual water vapor and then passed through 32 μm and 100 μm sieves to collect the powder with a particle size of 32-100 μm, thus obtaining the FSA / alumina ceramic composite powder. The SEM results are as follows: Fig.10 As shown;
[0090] Step 3: Determine particle size and flowability
[0091] The composite powder collected in step 2 was measured for particle size and fluidity by a laser particle size analyzer and a Hall flowmeter, respectively. The D50 and D90 of the composite powder measured by the laser particle size analyzer were 43.2 μm and 86.1 μm, respectively, and the fluidity was 96 s / 50 g.
[0092] Step 4: Atmospheric plasma spraying
[0093] After washing away the oil on the surface of the substrate with ethanol, acetone, etc., the substrate was sandblasted, and then the sandblasted substrate was fixed in the spraying range of the robotic arm. The powder feeding rate was measured to be 13g / min. The robotic arm program was set to include a distance of 12cm from the substrate, a step distance (mm) of 3*42, and a number of cycles (non-stop) of 6. Then, the spraying power was set to 55KW, and the argon, nitrogen, and hydrogen rates were 4529.6, 2264.8, and 1698.6L / min, respectively. After the setting was completed, the substrate was preheated, and then the bonding layer Ni@Al and the FSA / alumina ceramic composite powder functional layer were sprayed successively. The SEM results are shown in the figure. Fig.11 shown.
[0094] Comparative Example 3
[0095] Step 1: SiO2 shell coating
[0096] 2g PVP was uniformly dissolved in 1L deionized water under mechanical stirring at 300r / min. After fully dissolved, 100g FSA was added and reacted at room temperature for 30min. Then, 10g silicon particles were added when the water bath was heated to 70℃. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, FSA@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times, and then dried at 80℃ for use.
[0097] Step 2: Double-layer SiO2 shell coating
[0098] The FSA@SiO2 obtained in step 1 was uniformly dispersed in 1L of deionized water under mechanical stirring at 300r / min, and then 10g of silicon particles were added when the water bath was heated to 70°C. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, the FSA@SiO2@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times. It was dried at 80°C for use. Its density was measured to be 6.7g / cm 3 .
[0099] Comparative Example 4
[0100] Step 1: SiO2 shell coating
[0101] 2g PVP was uniformly dissolved in 1L deionized water under mechanical stirring at 300r / min. After fully dissolved, 100g FSA was added and reacted at room temperature for 30min. Then, 10g silicon particles were added when the water bath was heated to 70℃. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, FSA@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times, and then dried at 80℃ for use.
[0102] Step 2: Double-layer SiO2 shell coating
[0103] The FSA@SiO2 obtained in step 1 was uniformly dispersed in 1L of deionized water under mechanical stirring at 300r / min, and then 10g of silicon particles were added when the water bath was heated to 70°C, and then the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, the FSA@SiO2@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times, and then dried at 80°C for use.
[0104] Step 3: Three-layer SiO2 shell coating
[0105] The FSA@SiO2@SiO2 obtained in step 2 was uniformly dispersed in 1L of deionized water under mechanical stirring at 300r / min, and then 10g of silicon particles were added when the water bath was heated to 70°C. Then, the prepared ammonia solution was uniformly added to the mixed solution through a peristaltic pump. The concentration of the ammonia solution was 0.13mol / L, and the ammonia solution was added at a rate of 2mL / min. The reaction lasted for 2h. After filtering through a filter, the FSA@SiO2@SiO2@SiO2 was obtained after repeated washing with deionized water and magnetic collection for 3 times. It was dried at 80°C for use, and its density was measured to be 6.3g / cm 3 .
[0106] Result analysis: From Figure 1 , 5 The powder surface morphology of 9 can be clearly seen. With the coating of different coating layers, the powder surface morphology presents different forms, which proves the successful preparation of core-shell structure. On the other hand, Figure 4 , 8 12, it can be clearly seen that with the appearance of the shell layer, the dielectric constant of the magnetic alloy powder decreases significantly, which further proves the successful preparation of the core-shell structure and improves the impedance matching characteristics of the magnetic alloy powder, thereby further improving the performance of the coating. Fig.13 It can be seen that its magnetic properties have also been reduced to a certain extent. Fig.14 ,15 , 16, it can be seen that with the coating of the shell layer, the absorption intensity and effective bandwidth of the powder are improved. It can be seen from the composite powder figure and the coating structure figure that the preparation of the core-shell structure does not have an adverse effect on the composite powder and coating structure. In addition, from the comparison results of the density of each powder, it can be seen that with the increase of the thickness of the SiO2 shell layer, its density is further reduced (in color from yellow-brown-brown-blue-green), which is conducive to improving the sedimentation problem that occurs during the granulation process, so that the magnetic-dielectric component distribution of the composite powder is uniform. In addition, with the increase of the shell layer thickness, the shell layer density is also improved, thereby improving its oxidation resistance. In addition, the outer shell layer is selected from ZrO2 ceramic phase material on the one hand to reduce the dielectric properties of the magnetic alloy powder, on the other hand, ZrO2 has low thermal conductivity, thermal expansion coefficient and friction coefficient, and has a certain heat insulation effect, and a new interface is introduced between ZrO2 and SiO2. The interface effect is also conducive to excellent absorption performance and low infrared emissivity, taking into account radar infrared stealth, and realizing the multifunctionality of the coating.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. All modifications, equivalent substitutions, improvements, etc. within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a magnetic alloy / alumina composite thermal spraying powder, characterized in that: The steps include: S1, SiO2 shell coating Dissolve polyvinyl pyrrolidone PVP in deionized water by mechanical stirring, then add magnetic alloy powder and stir to react for a preset time, then heat up, add silicon particles, then drip ammonia solution of a prepared concentration into the mixture at a uniform speed through a peristaltic pump, and when the reaction is finished, obtain magnetic alloy @SiO2 by magnetic collection, and dry to obtain magnetic alloy @SiO2 powder; S2, ZrO2 shell coating Take ZrOCl2·8H2O and dissolve it in deionized water under mechanical stirring, then add the magnetic alloy @SiO2 powder obtained by S1, and then drip the prepared ammonia solution into the mixed solution at a uniform speed through a peristaltic pump. After the reaction is completed, the magnetic alloy @SiO2@ZrO2 is obtained by magnetic collection, and after drying, the magnetic alloy @SiO2@ZrO2 powder is obtained by heat treatment in an inert gas environment; S3. Composite powder preparation The magnetic alloy @SiO2@ZrO2 powder obtained by S2 and the ceramic binder Al2O3 are added to a ball mill, followed by adding polyvinyl alcohol PVA and then adding zirconium oxide balls, and rolling and stirring are performed to obtain a slurry; the obtained slurry is sent to a spray granulator for spray granulation, and dried and sieved to obtain a magnetic alloy @SiO2@ZrO2 / alumina ceramic composite powder, that is, a magnetic alloy / alumina composite thermal spraying powder.
2. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: In step S1, the magnetic alloy powder is a high Curie temperature iron-based magnetic alloy, and its particle size is less than 5 μm.
3. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 2, characterized in that: The high Curie temperature iron-based magnetic alloy is Sendust Aluminum (FSA).
4. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: The mass of the PVP is 1-5% of the magnetic alloy powder, the heating temperature is 70-85°C, the mass of the silicon particles is 3-10% of the magnetic alloy powder, the concentration of the ammonia solution is 0.1-0.15 mol / L, and the dripping rate of the ammonia solution is 1-3 mL / min.
5. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: In step S2, the concentration of ZrOCl2·8H2O is 0.06-0.1 mol / L, the concentration of ammonia water is 0.03-0.06 mol / L, and the dripping rate of ammonia water solution is 1-3 mL / min.
6. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: In step S2, the heat treatment conditions are: the gas environment is N2 atmosphere or H2 / Ar atmosphere, the treatment temperature is 300-650°C, and the heat treatment time is 2-4h.
7. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: In step S3, the solid content of the obtained slurry is 30-50%, of which the volume proportion of the magnetic alloy is 20-30%, and the mass of the PVA is 2-5% of the sum of the mass of the magnetic alloy @SiO2@ZrO2 powder and the alumina; the added amount of the zirconia ball satisfies: the ball-to-material ratio is 3-5:
1.
8. The method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 1, characterized in that: In step S3, the inlet and outlet temperatures of the spray granulator are controlled at 250° C. and 120° C., respectively, the feed rate is 35 mL / min, and the atomizer frequency is 25 Hz.
9. The magnetic alloy / aluminum oxide composite thermal spraying powder prepared by the method for preparing the magnetic alloy / aluminum oxide composite thermal spraying powder according to any one of claims 1 to 8, characterized in that: The particle size is 32~100μm.
10. The use of the magnetic alloy / aluminum oxide composite thermal spraying powder according to claim 9 for preparing a high temperature resistant multifunctional magnetic composite radar absorbing coating, comprising the following steps: Step A: Determine particle size and fluidity: The particle size and fluidity of the magnetic alloy / alumina ceramic composite powder are measured by a laser particle size analyzer and a Hall flow meter respectively; Step B, atmospheric plasma spraying: Use solvent to wash away the oil on the surface of the substrate, sandblast the substrate, and then fix the sandblasted substrate within the spraying range of the robotic arm, measure the powder feeding rate, set the robotic arm program, introduce the carrier gas, and then set the spraying power, carrier gas rate, and arc starting gas rate. After the settings are completed, preheat the substrate, and then spray the bonding layer and magnetic alloy / alumina ceramic composite powder in turn.
Citation Information
Patent Citations
Preparation method of SiO2-coated FeSiAl powder
CN109135348A
Magnetic powder surface gradient coating structure and coating method and soft magnetic composite
CN110405201A